GASP. V. Ram-pressure stripping of a ring Hoag's-like galaxy in a massive cluster. Issue 3 (10th January 2018) - Moretti, A; Poggianti, B M; Gullieuszik, M; Mapelli, M; Jaffé, Y L; Fritz, J; Biviano, A; Fasano, G; Bettoni, D; Vulcani, B; D'Onofrio, M
Abstract: Through an ongoing MUSE program dedicated to study gas removal processes in galaxies (GAs Stripping Phenomena in galaxies with MUSE, GASP), we have obtained deep and wide integral field spectroscopy of the galaxy JO171. This galaxy resembles the Hoag's galaxy, one of the most spectacular examples of ring galaxies, characterized by a completely detached ring of young stars surrounding a central old spheroid. At odds with the isolated Hoag's galaxy, JO171 is part of a dense environment, the cluster Abell 3667, which is causing gas stripping along tentacles. Moreover, its ring counter-rotates with respect to the central spheroid. The joint analysis of the stellar populations and the gas/stellar kinematics shows that the origin of the ring was not due to an internal mechanism, but was related to a gas accretion event that happened in the distant past, prior to accretion on to Abell 3667, most probably within a filament. More recently, since infall in the cluster, the gas in the ring has been stripped by ram pressure, causing the quenching of star formation in the stripped half of the ring. This is the first observed case of ram-pressure stripping in action in a ring galaxy, and MUSE observations are able to reveal both of the events (accretion and stripping) that caused dramatic transformations in this galaxy.